INTRODUCING SUSTAINABLE RICE PRODUCTION TO IMPROVE ENVIRONMENTAL AND SOCIO-ECONOMIC CONDITIONS IN KOCHANI VALLEY - Gjosheva Kovachevikj, Marija; Ilieva, Verica; Arsov, Saso (Goce Delchev University - Shtip, 2020)
Favourable climate conditions and the long tradition of rice cultivation as a main source of livelihood is essential base for a large portion of the population in the Kochani valley. The low productivity levels and high production costs put major limitations on the competitiveness on markets, mainly due to inadequate and obsolete cultivation practices applied. In addition, the common cultivation methods contribute to the destruction of environment and agroecosystems by intensive use of natural resources and agrochemicals. To that end, the NCP project implemented activities for adaptation of sustainable rice practices at 30 farmers, members in the association „Rice Tiller“, Cheshinovo, for the period of three years (2017-2019). Primarily, sustainable rice practices used by farmers consisted of: laser land levelling, use of certified seed material and reduced seed quantity, controlled use of fertilizers and agrochemicals and controlled use of water. Two sowing variants are implemented and tested, one by using seeding machine on dry soil and the another with manual seed broadcasting onto the watered soil. In this paper, data gained from the farmers’ passports, where regularly all agrotechnical measures and costs were recorded, are processed with the use of descriptive statistics and empirical methods of analysis. The outcomes demonstrate that the introduction of sustainable rice production results in efficient use of natural resources and reduced production costs, especially with dry-seeding method, which is fundamental for mitigation of food unsafety, biodiversity loss, soil degradation and environmental pollution, and at the same time for increasing rural households’ revenues.
Keywords: natural resources, Gross Margin, Cobb-Douglas production function, technical efficiency, allocative efficiency